2014
DOI: 10.1093/mmy/myu080
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent in situ hybridization of pre-incubated blood culture material for the rapid diagnosis of histoplasmosis

Abstract: Fluorescence in situ hybridization (FISH) has been shown to be useful for the detection of Candida and Cryptococcus species in blood culture materials. FISH procedures for the detection of Histoplasma capsulatum var. capsulatum have not been reported so far. This study describes the development and evaluation of fluorescently labeled rRNA-targeting FISH probes to detect and identify H. capsulatum in blood cultures. All three analyzed H. capsulatum reference strains and clinical isolates showed positive signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We conclude that sequence results obtained after panfungal PCR can only be considered as confirmatory information in case of matching with preliminary histological results owing to the high risk of contamination of paraffin blocks with environmental fungal spores. Other histological techniques such as immunohistochemistry [ 8 , 32 ] and in situ hybridization [ 8 , 33 ] or, alternatively, specific PCRs for formalin-fixed, paraffin-embedded tissues [ 8 , 29 ] can be used for the confirmation of diagnosis if mycological culture is not possible. Preliminary histological results should be interpreted with care and supported by cultural approaches whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that sequence results obtained after panfungal PCR can only be considered as confirmatory information in case of matching with preliminary histological results owing to the high risk of contamination of paraffin blocks with environmental fungal spores. Other histological techniques such as immunohistochemistry [ 8 , 32 ] and in situ hybridization [ 8 , 33 ] or, alternatively, specific PCRs for formalin-fixed, paraffin-embedded tissues [ 8 , 29 ] can be used for the confirmation of diagnosis if mycological culture is not possible. Preliminary histological results should be interpreted with care and supported by cultural approaches whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to culture and a criterion-based or clinical diagnosis of histoplasmosis, the sensitivity of molecular assays in published studies has ranged between 67 and 100% (30-35) and 33 and 87% (36,37), respectively. A fluorescence in situ hybridization (FISH) technique that successfully detects H. capsulatum rRNA in blood cultures may circumvent the need for colony growth to obtain a definitive and timely diagnosis (35). Although culture has typically been considered the gold standard for diagnosis, molecular methods may in fact be more sensitive.…”
Section: Molecular Methodsmentioning
confidence: 99%
“… 29 In comparison to culture or clinical diagnosis of histoplasmosis, the sensitivity of molecular assays in published studies has varied from 67% to 100%. 30 , 31 Some studies also showed that the sensitivity of molecular assays is 33 and 87%. 32 , 33 Histoplasmosis can be diagnosed through a combination of clear clinical presentation, positive culture results, or a typical histopathological examination.…”
Section: Discussionmentioning
confidence: 99%